Leveraging on macroeconomics determinants of prices of stocks in optimizing capital gains using the top 30 blue chip entities - Tiu, Carlo B.; Nepay, Cristina B.; Peleo, Pamela Ann B.; Quisay, Mac Clifford M.; Reyes. Junigem Fernan B.; Sales, Ma. Veronica R.; Sartin, Irish T. and Young, Paul Justine M.,. 4 0 16; 5
u
Research Paper: (BSBA major in Finance and Treasury Management)- Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2